2016
DOI: 10.3389/fvets.2016.00013
|View full text |Cite
|
Sign up to set email alerts
|

Rearing Laying Hens in Aviaries Reduces Fearfulness following Transfer to Furnished Cages

Abstract: Appropriate rearing is essential for ensuring the welfare and productivity of laying hens. Early experience has the potential to affect the development of fearfulness. This study tested whether rearing in aviaries, as opposed to cages, reduces the fearfulness of laying hens after transfer to furnished cages. Fear responses were recorded as avoidance of a novel object in the home cage. Lohmann Selected Leghorns were reared in an aviary system or conventional rearing cages and then transported to furnished cages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 24 publications
3
15
0
Order By: Relevance
“…Analysis of treatment effects on scores for Component 1 interpreted as fearfulness as discussed above, confirmed that aviary-reared birds housed in the more complex environment were less fearful than cage-reared birds at both ages. This corresponds well to findings by Brantsæter et al ( 32 ) in which cage-reared birds were more hesitant than aviary-reared birds to approach a NO in their home cage. The current study used PCA analysis to generate a fearfulness score that took account of six variables across two different test conditions in which birds were exposed to a variety of stimuli.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Analysis of treatment effects on scores for Component 1 interpreted as fearfulness as discussed above, confirmed that aviary-reared birds housed in the more complex environment were less fearful than cage-reared birds at both ages. This corresponds well to findings by Brantsæter et al ( 32 ) in which cage-reared birds were more hesitant than aviary-reared birds to approach a NO in their home cage. The current study used PCA analysis to generate a fearfulness score that took account of six variables across two different test conditions in which birds were exposed to a variety of stimuli.…”
Section: Discussionsupporting
confidence: 91%
“…The current study used PCA analysis to generate a fearfulness score that took account of six variables across two different test conditions in which birds were exposed to a variety of stimuli. The PCA score used in the present study may be a better measure of fearfulness than the single response variable used by Brantsæter et al ( 32 ), as the latter may be more stimulus specific.…”
Section: Discussionmentioning
confidence: 78%
“…Similarly, Hartcher and colleagues [11] found minimal impacts of enrichment with pecking strings, litter, and scattered oats on pullet responses in open field and tonic immobility tests. Aviary-rearing compared with cage-rearing reduced fearful responses toward novel objects in the first few weeks following transfer to a furnished cage system [12] and increased the use of the three-dimensional area in the experimental laying house [13]. However, there were no differences in faecal corticosterone metabolites, and the differences in system use were equivalent between rearing groups after four weeks in the new housing environment [13].…”
Section: Introductionmentioning
confidence: 96%
“…The least squares means ± SEM of body weight in pullets from three rearing enrichment treatments (control, novelty, structural) as measured at four different age points(5,8,12, and 16 weeks of age).…”
mentioning
confidence: 99%
“…Day-old chicks reared in either aviary systems or conventional cage systems (all birds kept on paper in cages up to 4 wk of age before aviary doors opened) were transferred to furnished cage systems at 16 wk of age (Brantsæter et al., 2016a,b). Fear of novel objects and humans was reduced in the aviary-reared birds when tested up to 5 wk following transfer compared to the cage-reared birds (Brantsæter et al., 2016a,b).…”
Section: Introductionmentioning
confidence: 99%